2018
DOI: 10.1111/trf.14526
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma unit distributions to hospitals over a 10‐year period

Abstract: Although the number of plasma unit distributions has decreased at many blood collectors over time, the proportion of AB units has increased at both ABCs and NPBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Similarly, although the quantity of transfused plasma continues to decrease, the proportion that is group AB increased. This observation has also been reported in other countries . The proportional increase might be attributable to massive transfusion protocols which require an available reserve supply of thawed plasma, which is often group AB plasma reserved for potential recipients with unknown ABO type …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, although the quantity of transfused plasma continues to decrease, the proportion that is group AB increased. This observation has also been reported in other countries . The proportional increase might be attributable to massive transfusion protocols which require an available reserve supply of thawed plasma, which is often group AB plasma reserved for potential recipients with unknown ABO type …”
Section: Discussionsupporting
confidence: 73%
“…48 The proportional increase might be attributable to massive transfusion protocols which require an available reserve supply of thawed plasma, which is often group AB plasma reserved for potential recipients with unknown ABO type. 48 During 2017, the majority of PLT units were transfused 4-5 days after collection. This contrasts with 2015, when the majority of PLT units were transfused ≤3 days after collection.…”
Section: Inventorymentioning
confidence: 99%
“…Group AB plasma has traditionally been considered the ‘universal donor’ plasma product, analogous to group O red cells. However, it is a scarce resource that has been in increasing demand, placing strain on blood donors and suppliers, which prompts the need for quality improvement initiatives to improve on its usage (Seheult et al ., ). Our study developed the use of the ABAI as a KQI to assess group AB plasma utilisation, which suggested inappropriate use and justified the need for intervention.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study of blood product utilisation demonstrated that plasma transfusion represents approximately half of blood products used during MTPs (Dunbar et al ., ). Blood centres worldwide have observed a relative increase in the proportion of AB plasma used despite an overall decrease in plasma units distributed over the last decade (Seheult et al ., ). An international study also demonstrates that the majority of AB plasma is administered to non‐group AB patients, mostly in settings where acutely bleeding patients are managed (Zeller et al ., ).…”
mentioning
confidence: 97%
“…Additionally, the uniform method did not reduce the interlaboratory titer variability in comparison to other methods per College of American Pathologists proficiency testing. Finally, various thresholds for what is considered a “high” titer for plasma‐containing products have been reported . Thus, the goals of this study were to survey the titer testing methods, the definitions of high‐titer antibodies that are currently in use, and the blood products being tested for high‐titer antibodies, and to elucidate the prevalence of high‐titer units that are identified using the local definition.…”
mentioning
confidence: 99%